Criticisms of digital art: Foundations and theoretical limits - Roncoroni Osio, Umberto (2021)
This article attempts a critical examination of the actual digital art production, posing key questions about its artistic value inside the contemporary esthetic discourse, including the relationships with the art system. Considering the properties of the numeric language, two important topics will be discussed: the dialectic artwork-process and the meaning of digital multimedia. With the support of up-to-date computational creativity theories and the evidences of experimental digital art, the treacherous influence of the romantic aesthetic paradigm and the traditional art system will be tested. As a possible solution, the author suggests rethinking the components of software as meta-medium, such as its information assets, its algorithms, the code textual properties, interactivity and interfaces. In the conclusions it will be stressed that the immateriality of software is paramount to avoid misunderstandings and to open new fields of research. For instance, natural computation, ethnomathematics and ethno-computing are valuable social and educational contents and meanings that could substantially improve digital art.